The Impact of Change Management on Employee Performance: An Explanatory Quantitative Study of State-Owned Enterprises in Indonesia - Putro, Suryati Eko; Suharyati, S. (Golden Ratio of Human Resource Management, 2026)
Organizational reform in State-Owned Enterprises (SOEs) is part of the Indonesian government's strategy to improve efficiency and competitiveness. However, this process often affects human resources, especially employee performance. This study analyzes the influence of change management on employee performance during restructuring in one SOE. The research applies a quantitative approach with an explanatory survey design. Data were collected through questionnaires from 120 permanent employees in units affected by restructuring. The analysis, using regression, indicates that change management has a significant positive effect on employee performance. Transformational leadership, effective communication, and employee involvement are identified as key factors that enhance productivity and motivation. These findings align with established change management theories and reinforce previous evidence in public sector contexts. The study concludes that well-implemented change management is critical to sustaining and improving employee performance during organizational transitions, offering practical insights for HR managers in SOEs to develop participatory and human-centered strategies.